A novel amylolytic enzyme from Palaeococcus ferrophilus with malto-oligosaccharide forming ability belonging to subfamily GH13_20. (February 2022) - Ji, Hangyan; Li, Xiaoxiao; Jiang, Tong; Fang, Qi; Bai, Yuxiang; Long, Jie; Chen, Long; Jin, Zhengyu
Abstract: By heterologous expression of a gene from Palaeococcus ferrophilus, a novel recombinant enzyme designated AMPf was obtained and proved to be an amylolytic enzyme with unique catalytic characteristics. The optimal temperature and pH of AMPf were 50 °C and 7.0 respectively. Although sequence analysis and acarbose hydrolysis ability indicated that AMPf belongs to the subfamily GH13_20, interestingly, this enzyme hardly acts on cyclodextrins and pullulan distinguishing it from most enzymes in this subfamily. AMPf hydrolyzes starches to glucose, maltose, maltotriose, and maltotetrose as main products. AMPf mainly liberates glucose from starch with the concentration of 1% (w/v), while it shows malto-oligosaccharide forming ability with higher starch concentration of 4% (w/v). Also, the 4, 6-ethylidene-4-nitrophenyl-maltoheptaose hydrolysis ability further indicates the unique combination endo-acting and glucose releasing exo-acting activtity of AMPf. AMPf could utilize maltose and maltotriose to produce malto-oligosaccharides by transglycosylation activity. It was proven AMPf has application protential in malto-oligosaccharides production. Graphical abstract: Image 1 Highlights: A novel amylolytic enzyme from Palaeococcus ferrophilus (AMPf) was discovered. AMPf was fully characterized and proved to be from subfamily GH13_20. AMPf was amylolytic enzyme with endo- and glucose releasing exo-acting activtity. AMPf mainly produced malto-oligosacchardes at high starch concentration. AMPf could use maltose and maltotriose to produce malto-oligosaccharides.